Geometrical behavior of laminated graphite/epoxy composite using hypermesh - Siva RamaKrishna, Ch; Subba Rao, KV; Arji, Saineelkamal (International Journal of Engineering and Technology, 2018)
The laminated composite material is Â made of ply which are specically used in automotive, aerospace and military applications due to less in weight and high strength to weight ratio. The role of structural strength is very important in composites, as the material is weak in inherent strength leads to damage of equipment made with the laminated composite. Hence, an accurate understanding of their structural geometrical behavior for residual stresses is required, such as residual stresses with different aspect ratios. In present work, various aspect ratios of laminated composite and its residual stresses are investigated using finite element analysis. The numerical results showed, on the residual stresses, that the effects the change the residual stresses due change of aspect ratio of laminated Graphite/epoxy composite.Â